Femtocell Number Influence to SINR and Throughput on Coexistence GSM and LTE Network - Muhammad Yaser (Jetri : Jurnal Ilmiah Teknik Elektro, 2020)
Coexistence GSM network and LTE femto relies on the number of femtocell deployment position. In the earlier study, the impact of macrocell size, femtocell deployment position, and coexistence LTE femtocell network integrated with GSM macrocell had been discussed. LTE femtocell used Orthogonal Frequency Division Multiplexing (OFDM) technology for its operation. In coexistence networks, LTE femtocells operate with OFDM technology so that they can utilize several radio frequency fractions without disturbing other parts of the frequency located between them. Unfortunately, the impact of femtocell number on the coexistence network had not been discussed. SINR and femtocell throughput performance are mathematically analyzed. The result showed that femtocell number had an effect on the coexistence network performance. SINR GSM, SINR femtocell and femtocell throughput significantly degraded as the femtocell number increased. The increasing femtocell number from M =0 to M =20 on each GSM cell cause around 14 dB degradation in SINR GSM, 3 dB decline in SINR Femto, approximately 1.7% decline in throughput for K = 4. Meanwhile for K = 7, the increasing femtocell number cause 17 dB decline in SINR GSM 6,5 dB decline in SINR Femto and 3.2 % decline in throughput. Those happened since the LTE femtocell interference went up. So femtocell number greatly influences the Coexistence GSM Network and LTE femtocell.Jaringan koeksistensi GSM dan LTE Femto sangat tergantung pada kondisi sebaran femtocell, di antaranya jumlah femtocell. Pada studi sebelumnya telah dibahas mengenai pengaruh ukuran macrocell dan posisi penyebaran femtocell dan jaringan koeksistensi LTE femtocell yang diintegrasikan dengan GSM macrocell. Dalam jaringan koeksistensi, LTE femtocell beroperasi dengan teknologi Orthogonal Frequency Division Multiplexing (OFDM) sehingga dapat memanfaatkan beberapa fraksi frekuensi radio tanpa mengganggu bagian lain dari frekuensi yang terletak di antaranya Namun studi sebelumnya belum membahas pengaruh jumlah femtocell pada jaringan koeksistensi ini. Kinerja kedua sistem yang dalam hal ini SINR dan femtocell throughput dianalisis secara matematis. Hasil simulasi menunjukan bahwa jumlah femtocell memiliki efek pada kinerja jaringan koeksistensi. SINR GSM, SINR femtocell dan femtocell throughput semakin menurun seiring dengan peningkatan jumlah femtocell. Peningkatan jumlah femtocell dari M = 0 ke M = 20 pada setiap sel GSM menyebabkan penurunan sekitar 14 dB SINR GSM, penurunan 3 dB SINR Femto, sekitar1, 7% penurunan throughput untuk K = 4. Sementara itu untuk K = 7, peningkatan junlah femtocell menyebabkan penurunan 17 dB SINR GSM, penurunan 6.5 dB SINR Femtocell dan penurunan 3, 2% dalam throughput. Hal ini disebabkan oleh peningkatan interferensi dari LTE femtocell. Maka jumlah LTE femtocell sangat mempengaruhi sistem koeksistensi LTE femtocell dengan jaringan GSM.